IMPROVING METHODS OF RISK FORECASTING IN FINANCIAL RELATIONS OF BUSINESS ENTITIES - Abdullayeva Madinabonu Khasanbayevna (European Science Publishing, 2024)
This article explores the significance of effective risk forecasting in financial relations among business entities. It delves into current methodologies, their limitations, and proposes innovative approaches for more accurate risk assessment. By synthesizing existing literature and proposing novel methods, this article aims to contribute to the advancement of risk management practices in the realm of business finance.
Keywords: Risk forecasting, financial relations, Business entities, Risk management, Methodologies.